Simultaneous analysis of frequency and voltage control of the interconnected hybrid power system in presence of FACTS devices and demand response scheme - Sudhanshu Ranjan (Elsevier, 2021)
This work confers the simultaneous analysis of voltage and frequency control of the 3-area interconnected hybrid power system (IHPS) consisting of parabolic-trough solar power system (PSP), wind power system (WPS) and dish-stirling solar power system (DSP) under the paradigm of microgrid. The speculated result of the IHPS is presented and analyzed considering real and reactive power as the function of both voltage and frequency. 9The proposed IHPS under investigation has been mathematically modeled for direct coupling like active power–frequency and reactive power–voltage relationships and cross coupling like active power–voltage and reactive power–frequency​ relationships. The system responses under different operating conditions have been investigated to see the cross-coupling behavior of the proposed IHPS in the presence of voltage compensating devices like dynamic voltage restorer (DVR) and Static Synchronous Compensator (STATCOM). Further, Demand Response Scheme (DRS) as a frequency control strategy has been considered to enhance the system stability. System responses have been critically analyzed under Mine Blast Algorithm (MBA) based proportional–integral–derivative (PID) controllers